Back on Tito Street: bodies and citizens. Issue 3 (2nd September 2019) - Štiks, Igor
ABSTRACT: Inspired by militant research and personal experience, this article explores how bodies become political in an urban environment where space and time interact to form specific, socially and politically charged chronotopes. The political relationship between the chronotope of and the bodies on Tito Street in Sarajevo is narrated here through a series of photos of defining moments in the modern history of the city, from its liberation in 1945, through the socialist period, to its siege and recent protest movements. The author stresses that the corporeal performances and acts of citizens acquire their true social and political meaning only within a concrete chronotope that attaches emotions and values to their actions. These emotions and values constitute a certain political culture formed from the struggles of, in this case, progressive, emancipatory and left-wing forces. In the face of these struggles, the author claims that researchers and observers cannot remain neutral, and further elaborates his own personal and political engagement.